Black hairy tongue syndrome - Gurvits, Grigoriy E (Baishideng Publishing Group Inc, 2014)
Black hairy tongue (BHT) is a benign medical condition characterized by elongated filiform lingual papillae with typical carpet-like appearance of the dorsum of the tongue. Its prevalence varies geographically, typically ranging from 0.6% to 11.3%. Known predisposing factors include smoking, excessive coffee/black tea consumption, poor oral hygiene, trigeminal neuralgia, general debilitation, xerostomia, and medication use. Clinical presentation varies but is typically asymptomatic, although aesthetic concerns are common. Differential diagnosis includes pseudo-BHT, acanthosis nigricans, oral hairy leukoplakia, pigmented fungiform papillae of the tongue, and congenital melanocytic/melanotic nevi/macules. Clinical diagnosis relies on visual observation, detailed history taking, and occasionally microscopic evaluation. Treatment involves identification and discontinuation of the offending agent, modifications of chronic predisposing factors, patient’s re-assurance to the benign nature of the condition, and maintenance of adequate oral hygiene with gentle debridement to promote desquamation. Complications of BHT (burning mouth syndrome, halitosis, nausea, gagging, dysgeusia) typically respond to therapy. Prognosis is excellent with treatment of underlying medical conditions. BHT remains an important medical condition which may result in additional burden on the patient and health care system and requires appropriate prevention, recognition and treatment.